Regression Estimates of the Elasticity of Taxable Income and the Choice of Instrument - Simon Carey; John Creedy; Norman Gemmell; Josh Teng (New Zealand Government, The Treasury, 2013)
This paper examines estimation of the elasticity of taxable income using instrumental variable regression methods. It is argued that the standard instrument for the net-of-tax rate - the rate that would be applicable post-reform but with unchanged income levels - is unsatisfactory in contexts where there are substantial exogenous changes in taxable income. Two alternative tax rate instruments are proposed, using estimates of the dynamics of taxable income for a panel of taxpayers over a period that involves no tax changes. The parameters derived from this procedure are then used to construct counterfactual post-reform incomes that would be expected in the absence of reform. The first method is based on the tax rate each individual would face if income were equal to expected income, conditional on income in two periods before the tax change. The second alternative uses the form of the conditional distribution of income for each taxpayer to obtain an instrument based on the expected tax rate. The methods are applied to the tax change in New Zealand in 2001. It is found that the proposed new instruments significantly outperform the standard instrument, in particular there are substantial improvements using the expected tax rate.
Keywords: H24; H31; 330; Income taxation; taxable income; elasticity of taxable income; instrumental variables; tax rate instruments.; Einkommensteuer; Besteuerungsverfahren; Elastizität; IV-Schätzung; Neuseeland